PENGARUH MACAM LANJARAN DAN MULSA PADA HASIL MENTIMUN VAR. ORIS (Cucumis sativus, L.) - Ahmadi Ahmadi; Murti Astiningrum; Yulia Eko Susilowati (JURNAL VIGOR, 2016)
A study on the effects of plant support and mulch on the yield plant of cucumber (Cucumis sativus, L.) var. oris was conducted in March - June 2015. The research was in Kembangkuning Village, District Windusari, Magelang. The altitude is 640 m, the soil type is latosol and soil pH is 6.5. The research is factorial (2 x 4) experiment arranged in a complete randomized block design with three replications. The first factor is kind plant support: bamboo and plastic net. The second factor is kinds of mulch, rice straw, black plastic, silveric black plastic and transparent plastic mulch. Plant support from bamboo may increase crop growt that cause higher the weight per fruit and fruit volume. Black plastic mulch and silveric black plastic mulch may increase plant height, leaf number, weight of the fruit, weight per fruit and fruit volume. The highest fruit volume is obtained from the growth of cucumber supported by plastic net on black plastic mulch and silveric black plastic mulch.